MoS2 supported on MOF-derived carbon with core-shell structure as efficient electrocatalysts for hydrogen evolution reaction. (8th November 2018) - Feng, Jianhui; Zhou, Hu; Wang, Jinpei; Bian, Ting; Shao, Jinxiao; Yuan, Aihua
Abstract: In this work, the porous carbon polyhedra were firstly obtained by carbonizing the zeolite imidazole framework (ZIF-8). Then the carbon polyhedra and precursors of MoS2 were successfully combined by a hydrothermal reaction, forming the C-MoS2 composites with different carbon contents. The well-tuned C-MoS2 sample possesses a core-shell morphology, in which the carbon substrate is well decorated by vertically aligned MoS2 ultrathin nanosheets. The resulting composites can be used as electrocatalysts of hydrogen evolution reaction (HER), displaying significantly superior activities to pure MoS2 and carbon. It's found that the carbon content largely affects the architectures and HER behaviors of catalysts. In particular, the optimized catalyst yields the best catalytic activity with the lowest onset potential (35 mV), smallest Tafel slope (53 mv dec −1 ), lowest overpotential (200 mV at 10 mA cm −2 ), as well as extraordinary long-term stability in H2 SO4 . The enhanced HER activity can be attributed to the unique core-shell structure, where abundant active edge sites of MoS2 are exposed and the underlying carbon substrate effectively improves the conductivity of the electrode. Graphical abstract: A series of MOF-derived carbon-MoS2 composites are fabricated through a hydrothermal process. The optimized carbon-MoS2 catalyst exhibits a well-defined core-shell structure and delivers the best HER performance. Highlights: MOF-derived carbon-MoS2 composites are fabricated through a hydrothermal process. All C-MoS2 composites display superior catalytic activities toward HER to pure MoS2 . The morphologies and HER activities can be adjusted by the MoS2 /carbon mass ratio. The optimized catalyst has a core-shell structure and the best HER activity.